Agrochemical Management Combating the Challenges of Organic Farming - Dr P.S. Rajpoot (International journal of economic perspectives, 2020)
by protecting crops from insects, pests, fungi, weed, rodents etc. Owing to their benefits, they have been used indiscriminately rising concerns over their usage. Nevertheless, they are indispensable in agriculture to maintain productivity as the population is exponentially increasing and so is the demand for food. Hence there is a need to employ a policy for the management of the agrochemicals to encourage their judicious use.